2023
DOI: 10.3390/molecules28083544
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Antioxidant Activity in the Fruit of Rosehip (Rosa canina L. and Rosa rubiginosa L.)

Abstract: Rosehips (Rosa spp., Rosaceae) are wild rose bushes with more than 100 species. Its fruits vary in colour and size, depending on the species, and are recognised for their nutritional characteristics. Ten samples of Rosa canina L. and Rosa rubiginosa L. fruits were collected at different geographical points from Southern Chile. Nutrients such as crude protein and minerals and functional properties such as phenolic compounds, ascorbic acid, and also antioxidant activities were evaluated by HPLC-DAD-ESI-MS/MS. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…However, citric acid was immediately after quinic acid. Peña et al [ 27 ] reported that the total organic acid content of R. canina and R. rubiginosa ranged from 46.2 g/kg to 73.2 g/kg FW. Okatan et al [ 28 ] reported that the citric acid content in their samples of R. canina was between 15.9 and 22 g/kg FW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, citric acid was immediately after quinic acid. Peña et al [ 27 ] reported that the total organic acid content of R. canina and R. rubiginosa ranged from 46.2 g/kg to 73.2 g/kg FW. Okatan et al [ 28 ] reported that the citric acid content in their samples of R. canina was between 15.9 and 22 g/kg FW.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic content was between 1.1 g/kg FW and 2.2 g/kg FW. Pena et al [ 27 ] reported the total phenolic content in Rosa spp. Varied between 0.3 g/kg and 14 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis, the juice was first filtered two times through a 0.45 µm MCE disc filter (Biofil, Madrid, Spain). High-performance liquid chromatography with diode array detection (HPLC-DAD) analyses were performed using an HPLC system (Shimadzu, Tokyo, Japan) equipped with an LC-20AT quaternary pump, a DGU-20A5R degassing unit, a CTO-20A oven, a SIL-20 autosampler, and an SPD-M20A UV-visible diode array spectrophotometer, using a Kromasil C 18 (100 × 4.6 mm, 2.5 µm) column with a Novapak, Waters C 18 (22 × 3.9 mm, 4 µm) guard column at 40 • C. The flow rate was set at 0.8 mL min −1 , as reported by Peña et al [8]. Phenolic compounds were quantified by external calibration at a maximum wavelength for each family of compounds (360 nm for flavonols, 320 nm for hydroxycinnamic acid, and 280 nm for flavan-3-ols) using quercetin, chlorogenic acid (5-caffeoylquinic acid), and catechin as standards.…”
Section: Determination Of Phenolic Compounds By Hplcmentioning
confidence: 99%
“…The rosehip is classified as a non-wood forest product (PFNM) and represents an important commercial product for Chile, representing USD 28.9 million in revenue in 2022, which is an increase of 15.0% compared to that in 2021 [ 3 ]. The rosehip fruit has been the subject of scientific interest in recent years given its nutritional composition and functional properties [ 4 , 5 , 6 , 7 , 8 ]. Recent studies have reported high concentrations of calcium, magnesium, phosphorus, potassium, and proteins [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rosehip (Rosa canina L.) is a pseudofruit derived from the rose plant, scientifically recognized for its abundance of polyphenols, vitamin C, and a diverse array of bioactive compounds [1][2][3]. Most often found as a wild shrub, Rosa canina L. is now gaining popularity as an industrial crop [4].…”
Section: Introductionmentioning
confidence: 99%